Ultra-stable L-proline protected copper nanoclusters and their solvent effect. (28th June 2018) - Han, Bingyan; Peng, Tingting; Li, Ying; Yu, Mingbo; Hu, Xixi; He, Gaohong
Abstract: Water-soluble and ultra-stable L-proline-protected copper nanoclusters (Cu NCs) are reported, which overcome the bottleneck that Cu NCs are easily oxidized. The average size of Cu NCs is found to be 1.88 ± 0.17 nm. The as-prepared Cu NCs exhibit an excellent stability over the physiologically relevant pH range, long storage time, high ionic strength, high concentration of hydrogen peroxide and various common metal ions. The fluorescence intensity of Cu NCs maintains no change after 5 months stored in the refrigerator. Interestingly, the Cu NCs show a pH-dependent fluorescence behavior between 9 and 13, and the reversible process can be repeated for 8 consecutive cycles with the excellent reversibility of the fluorescence intensity. Moreover, the as-prepared Cu NCs display the solvent-dependent properties in the dimethyl sulfoxide and ethylenediamine, where the emission color turn to be green and yellow from blue, respectively. This unique fluorescence property of Cu NCs will make them serve as good probes in analytical applications.